2018
DOI: 10.3390/molecules24010038
|View full text |Cite
|
Sign up to set email alerts
|

Abelmoschus esculentus (L.): Bioactive Components’ Beneficial Properties—Focused on Antidiabetic Role—For Sustainable Health Applications

Abstract: The main features of the okra, Abelmoschus esculentus (L.), are highlighted. The evaluation of interactions between biologically active compounds and other components of the food matrix can be considered as the first action in the investigation of potential benefits of this annual herb. Moreover, updated examples of current and innovative directions in an integrated and multidisciplinary approach are discussed, with particular attention to chemometrics. Among the main effects attributed to okra, its antidiabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 90 publications
1
55
0
Order By: Relevance
“…It is important to bear in mind that the components of nanoparticles might be as toxic as the loaded bioactives [69]. In the present work, it is shown that the nanoparticle's components did not damage this cell line, in the range of tested concentrations (5,10,15, and 20 µg/mL, selected according to the literature [62]) as cell viability, at the highest concentration and 48 h exposure is about 95% of control (Figure 4, upper panel). Within the first 24 h of exposure to sucupira oil-NLC, the decrease of cell viability was~5% (highest difference recorded for sucupira oil-NLC at 20 µg/mL).…”
Section: Resultssupporting
confidence: 48%
See 2 more Smart Citations
“…It is important to bear in mind that the components of nanoparticles might be as toxic as the loaded bioactives [69]. In the present work, it is shown that the nanoparticle's components did not damage this cell line, in the range of tested concentrations (5,10,15, and 20 µg/mL, selected according to the literature [62]) as cell viability, at the highest concentration and 48 h exposure is about 95% of control (Figure 4, upper panel). Within the first 24 h of exposure to sucupira oil-NLC, the decrease of cell viability was~5% (highest difference recorded for sucupira oil-NLC at 20 µg/mL).…”
Section: Resultssupporting
confidence: 48%
“…Essential oils (EOs) are odorant liquid oily products, consisting of a complex mixture of lipophilic and volatile compounds obtained from a plant raw material by one of three distinct procedures: Dry distillation, driving by steam of water or suitable mechanical method without heating [1][2][3][4][5][6]. Among their most abundant constituents, terpenes, sesquiterpenes and flavonoids are receiving increasing attention as potential natural agents for the treatment of several human diseases [7][8][9][10][11][12][13][14][15] (e.g., rheumatoid arthritis and other inflammatory diseases, cardiovascular diseases, diabetes and metabolic syndrome [16][17][18]). Among chronic diseases, diabetes mellitus (DM) is recognized the epidemy of the 21st century.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fruit mucilage includes flavonoids, d-galactose, l-rhamnose, and d-dalacturonic acid. Okra leaves contain tannins, minerals, and flavonol glycosides (Durazzo et al, 2018;Purkait, Das, Ali, & Chakraborty, 2016;Saha, Jain, & Jain, 2011). Documented evidence revealed that okra has an ability to overcome metabolic syndrome symptoms.…”
mentioning
confidence: 99%
“…Additional factors that play an important role in the setting up of type 2 diabetes mellitus (T2DM) include the chronic hyperglycemia itself but also obesity which is recognised as a risk factor for the insulin resistance development and T2DM. Many natural products of nutraceutical interest [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] have been proposed worldwide for the management of diabetes, as evidenced in a recent quantitative literature analysis [29]. Hyperglycemia contributes to glycosylation of proteins and lipids, enhances the production of reactive oxygen species, encourages the synthesis and secretion of pro-inflammatory cytokines and also acute phase proteins in various tissues, which promote inflammation processes in the vascular wall [30,31].…”
Section: Introductionmentioning
confidence: 99%